Social ties and short-term self-reported delinquent behaviour of personality disordered forensic outpatients - Bouman, Yvonne H. A. (Legal and criminological psychology, 2010)
Purpose. In community-based forensic psychiatry, patients' social ties are considered as protective factor in a risk management strategy. However, it is unknown whether these ties actually assist patients to refrain from re-offending. We hypothesised a protective role for social ties in re-offending behaviour. Methods. In a sample of forensic outpatients with a personality disorder (N = 55), the relationship between social ties (social contacts and participation in social institutions) and short-term self-reported re-offences was studied within a prospective study design with a 6-month follow-up period. Results. Our results provide evidence for a protective function of club participation. For violent re-offences, social institutions were protective and this protective function remained, even when a patient had network members with a criminal background. Except for work-related contacts, social contacts did not provide protection. Conclusions. The protective effect of social ties, especially club participation, on desistance from re-offending in forensic psychiatric patients merits further attention from researchers and clinicians.